2014
DOI: 10.15270/50-2-399
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Elder Abuse and Neglect in the Informal Caregiving Setting

Abstract: This article provides an overview of factors contributing to elder abuse and neglect within the informal caregiving setting from the perspective of ecological theory. This theory offers a deeper understanding of the complexity of elder abuse by considering the interactions that take place across a number of interrelated systems as well as the multiple risk factors that contribute to elder abuse and neglect. Researchers, policy makers and practitioners need to develop awareness of the risk factors regarding eld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
1
12
0
3
Order By: Relevance
“…CWs’ experiences occur at three levels, namely: the caregiving context (micro) , organisational context ( meso ) , broader societal context (exo) and policy and structural context (macro) [16, 17]. Within the caregiving context , caregiving is inherently burdensome and stressful due to the suffering and dying of care recipients [18], the complexity of dementia care [19], and the emotional demands of caregiving [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CWs’ experiences occur at three levels, namely: the caregiving context (micro) , organisational context ( meso ) , broader societal context (exo) and policy and structural context (macro) [16, 17]. Within the caregiving context , caregiving is inherently burdensome and stressful due to the suffering and dying of care recipients [18], the complexity of dementia care [19], and the emotional demands of caregiving [20].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, job satisfaction influences CWs’ caring motivations and the quality of care they provide to older adults [26, 27]. The broader societal context of caregiving involves structural issues such as gender, ageism, and external support systems that influence CWs’ interaction with care recipients [16]. For example, stigmatisation of CWs in wider society could demotivate CWs [28].…”
Section: Introductionmentioning
confidence: 99%
“…rape and coerced nudity, 3) psychological/emotional abuse i.e. verbal harassment or humiliation, 4) abandonment, neglect or failure to provide adequate care, and 5) financial abuse or exploitation [27,28]. The impact of trauma may be worsened because of shame and fear, causing a reluctance to seek help, [14] and it has been reported that victims of elder abuse are more likely die prematurely than people who are not [27].…”
Section: The Challenge Of Elder Abusementioning
confidence: 99%
“…Risk factors that may increase the potential for abuse of an older person can be identified at different levels and include: individual; poor physical and mental health of the victim, mental disorders and alcohol/substance abuse in the abuser etc., relationship; shared living situations, poor family relationships etc., community; social isolation of caregivers and older persons, and socio-cultural beliefs and practices [27][28][29][30].…”
Section: The Challenge Of Elder Abusementioning
confidence: 99%
“…All forms of abuse are present among the aging population, but seeing that pensioners are often the only persons with an income in many households, financial abuse is most evident (Schenck & Louw, 2010:370). Abuse of the elderly can also be detected, seeing that these services are in frequent contact with older community members (Ananias & Strydom, 2014). This saves a lot of money for the government as people does not need to be admitted to a hospital or residential care facility.…”
Section: Theme 4: Advantages Of These Servicesmentioning
confidence: 99%